Molecular Markers of Dental Pulp Tissue during Orthodontic Tooth Movement: A Pilot Study - Rohaya Megat Abdul Wahab; Shahrul Hisham Zainal Ariffin; Wong Woan Yeen; Nurul Atikah Ahmad; Sahidan Senafi (The Scientific World Journal)
Three specific orthodontic tooth movement genes, that is, FCRL1, HSPG2, and LAMB2 were detected at upper first premolar (with appliance) dental pulp tissue by using GeneFishing technique as compared to lower first premolar (without appliance). These three differentially expressed genes have the potential as molecular markers during orthodontic tooth movement by looking at molecular changes of pulp tissue.